Juridical Analysis of Online Gambling Crimes Based on Decision Number 100/Pid.Sus/2024/Pn Sda - Arly Andreas Lumban Toruana; Mochammad Fahmi Ulum; Berardy Shane Haposan Aritonang; Rosmalinda; Annisa Hafizhah (Journal of Law Perspectives Review, 2026)
The rapid advancement of digital technology has contributed to the increasing prevalence of online gambling in Indonesia, giving rise to significant social and legal challenges. This study examines the criminal liability of online gambling perpetrators based on Court Decision Number 100/Pid.Sus/2024/PN Sda and evaluates the appropriateness of the legal reasoning adopted by the court. This research employs a normative juridical method with a statutory and case approach by analyzing the Criminal Code (KUHP), the Information and Electronic Transactions Law (ITE Law), and relevant judicial decisions. The findings indicate that the judge correctly applied the constituent elements of the online gambling offense under Article 303 of the Criminal Code and Article 27 paragraph (2) in conjunction with Article 45 of the ITE Law, supported by electronic evidence and witness testimony. The decision affirms that active participants in online gambling activities may be held criminally liable under both the Criminal Code and the ITE Law. This study contributes theoretically by clarifying the construction and application of the lex specialis principle in online gambling cases and offers practical insights for law enforcement officials in assessing electronic evidence similar cases.